Exploring Gender Stereotypes among Prospective Foster Families - Yaroshenko, Alla; Semigina, Tetyana (Socialinė teorija, empirija, politika ir praktika, 2023)
One of the acute social work issues in Ukraine is the deinstitutionalization of care for orphans and children left without parental care and the introduction of family care models. It is known that the success of such models largely depends on the motivations and values that inspire parents to place children, the socio-psychological characteristics of family members, gender aspects such as the distribution of household workload, the involvement of men in performing housework and care for children and so on.Building on social role theory, we examine gender stereotypes of prospective foster parents in Kyiv, Ukraine. The exploration of femininity and masculinity stereotypes was carried out using the Sex-Role Inventory (Bem, 1974), while the assessment of ambivalent sexism in the attitudes toward women and men was done through using a short version of the methodology of Glick and Fiske (1996). 83 paricipants of the mandatory trainings for prospective foster parents were questioned.Our study reveals that the prospective foster parents hold a biased set of beliefs. Almost a third of respondents’ responses concerning women show high indicators on the femininity scale and concerning men – on the masculinity scale. Also, respondents demonstrate a greater extent of benevolent rather than hostile sexism and describe a generalized image of women and men as androgynous individuals. High levels of hostility to feminism, especially among women, have been reported.Ukraine has all legal grounds for gender equality. Thus, from the intersectional point of view, the study results highlight the impact of culture and social norms on perceptions of gender and gender stereotyping.The paper ends with suggestions on training programs for both prospective foster parents and social workers, enchancing egalitarian family patterns and agency of women.
Keywords: gender stereotypes; social roles; femininity; masculinity; foster care